2017
DOI: 10.1186/s13567-017-0452-3
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of serological responses to Coxiella burnetii and shedding at kidding among intensively-managed goats supports early use of vaccines

Abstract: Vaccination against Coxiella burnetii, the cause of Q fever, is reportedly the only feasible strategy of eradicating infection in ruminant herds. Preventive vaccination of seronegative goats is more effective in reducing shedding of C. burnetii than vaccinating seropositive goats. The age at which goats born on heavily-contaminated farms first seroconvert to C. burnetii has not yet been documented. In a 16-month birth cohort study, the age at which goats seroconverted against C. burnetii was investigated; 95 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
2
10
1
1
Order By: Relevance
“…In humans, phase II is associated with acute Q fever, with phase II-specific IgG antibodies appearing earlier and persisting at higher titers than phase I antibodies ( 55 ). A similar antibody response has also been demonstrated in mice and goats ( 56 , 57 ). The macropods included in this study demonstrated a larger proportion seropositive to phase I antigen, compared to phase II antigen, with no animals positive for phase II antibody only.…”
Section: Discussionsupporting
confidence: 75%
“…In humans, phase II is associated with acute Q fever, with phase II-specific IgG antibodies appearing earlier and persisting at higher titers than phase I antibodies ( 55 ). A similar antibody response has also been demonstrated in mice and goats ( 56 , 57 ). The macropods included in this study demonstrated a larger proportion seropositive to phase I antigen, compared to phase II antigen, with no animals positive for phase II antibody only.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, no clinical signs related to toxoplasmosis, neosporosis or Q fever were detected in any analyzed flocks, which can be related to several variables, such as stage of infection, pathogen strains, seroconversion and the animal immunity, as previously reported in the literature (Bezerra et al, 2013;Porto et al, 2016;Muleme et al, 2017). The absence of clinical reproductive signs (e. g. abortions and infertility) and their relationship with these mentioned variables (particularly with seroconversion) suggests also the presence of persistent or latent infected goats in these flocks, but their confirmation using immunoblot techniques are necessary to assess this hypothesis.…”
Section: Discussionsupporting
confidence: 64%
“…In this way nonpregnant goats that are infected with C. burnetii before breeding, could play a role in the dynamics of Q fever in a goat herd although the exact attribution of pre-bred infected goats cannot be derived from this study. This risk can be further reduced by vaccinating the kids as early as possible, which Muleme et al have already suggested as an approach for eradicating Q fever from an infected herd [22].…”
Section: Discussionmentioning
confidence: 99%